Anti-proliferation and anti-inflammation effects of corilagin in rheumatoid arthritis by downregulating NF-κB and MAPK signaling pathways. (10th February 2022) - Shen, Yue; Teng, Li; Qu, Yuhan; Liu, Jie; Zhu, Xudong; Chen, Shan; Yang, Longfei; Huang, Yuehui; Song, Qin; Fu, Qiang
Abstract: Ethnopharmacological relevance: The dried aboveground part of Geranium Wilfordii Maxim. ( G. Wilfordii ) is a traditional Chinese herbal medicine named lao-guan-cao. It has long been used for dispelling wind-dampness, unblocking meridians, and stopping diarrhea and dysentery. Previous investigations have revealed that 50% ethanolic extract of G. Wilfordii has anti-inflammatory and anti-proliferation activities on TNF-α induced murine fibrosarcoma L929 cells. Corilagin (COR) is a main compound in G. Wilfordii with the content up to 1.69 mg/g. Pharmacology study showed that COR has anti-inflammatory, anti-tumor, anti-microorganism, anti-oxidant, and hepatoprotective effects. However, there is no any investigation on its anti-proliferation and anti-inflammation effects in rheumatoid arthritis (RA). Aim of the study: The present study aimed to evaluate the potential pharmacological mechanisms of anti-proliferation and anti-inflammation effects of COR in RA. Materials and methods: In vitro, MH7A cells model induced by IL-1β was used. The anti-proliferation activity of COR was assessed by Cell Counting Kit-8 (CCK-8) assay, and the anti-migration and anti-invasion activity of COR was determined by wound healing assay and transwell assay, respectively. Furthermore, apoptosis assay by flow cytometer was used to measure the pro-apoptotic effect of COR. The mRNA expressions of Bax, Bcl-2, IL-6, IL-8, MMP-1, MMP-2, MMP-3, MMP-9, COX-2, and iNOS were measured by qRT-PCR, and related protein were further verified by ELISA kits or Western blot. Moreover, protein levels associated with NF-κB and MAPK signaling pathways of p65, P-p65, IκBα, P-IκBα, ERK1/2, P-ERK1/2, JNK, P-JNK1/2/3, p38, and P-p38 were determined by Western blot. The nuclear translocation of NF-κB-p65 was detected by immunofluorescent staining. In vivo, adjuvant-induced arthritis (AIA) rat model was used, and the body weight, paw swelling, and arthritis score during the entire period were measured. Histopathological analysis of joints of synovial tissues was also determined. The expression of pro-inflammatory cytokines in serum including IL-6, TNF-α, IL-1β, and IL-17 were measured. Results: The in vitro results showed that COR could dose-dependently inhibit the proliferation, migration, and invasion of IL-1β-induced MH7A cells, as well as promote its apoptosis. Moreover, it also suppressed the over-expression of Bcl-2, IL-6, IL-8, MMP-1, MMP-2, MMP-3, MMP-9, COX-2, and iNOS while up-regulated the level of Bax. Besides, the ratios of P-p65/p65, P-IκBα/IκBα, P-ERK/ERK, P-JNK/JNK, and P-p38/p38 were decreased, and the nuclear translocation of p65 induced by IL-1β was blocked by COR. In vivo results indicated that COR significantly reduced the paw swelling and arthritis score in AIA rats, and inhibited synovial tissue hyperplasia and erosion, as well as inflammatory cells infiltration. It also decreased the serum pro-inflammatory cytokines (IL-6, TNF-α, IL-1β, and IL-17) production. Conclusion: These results revealed that COR exerted anti-rheumatoid arthritis effect, and its underlying mechanisms may be related to inhibiting the proliferation, migration, and invasion of synovial fibroblasts, enhancing cell apoptosis, and suppressing inflammatory responses via downregulating NF-κB and MAPK signaling pathways. Graphical abstract: Image 1